PERANCANGAN SISTEM INFORMASI PENGELOLAAN DISTRIBUSI BARCODE BBM DI SPBU SUKOREJO SITUBONDO - Mutimatus Solehah; Ahmad Lutfi; Irma Yunita (Jurnal Riset Teknik Komputer, 2025)
Efficient and targeted fuel distribution is a challenge at the Sukorejo Situbondo gas station, particularly in terms of monitoring subsidy quotas and recording transactions, which are still done manually. This research aims to design a fuel barcode distribution management information system to improve efficiency, accuracy, and transparency in the fuel distribution process. This system utilizes barcode technology that enables consumer verification, monitoring subsidy usage, and automatic and integrated transaction recording. The software used in this system is a web-based application connected to a MySQL database for data storage, as well as PHP for server-side programming and JavaScript for the user interface (frontend). It is expected that this system can speed up the service process, reduce human error, and assist in better transaction data management and reporting, thereby supporting more effective and efficient fuel management at the Sukorejo Situbondo gas station.